Design of a 50 Wp Off-Grid Solar Power Plant Using a Linear Actuator Solar Tracker System - Muhammad Fajry Setiawan; Maulana Adi Prakoso; Komarudin Komarudin; Erfiana Wahyuningasih (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Conventional solar power plants (PLTS) generally use fixed-angle solar panels that follow the roof inclination, limiting their ability to capture maximum solar radiation throughout the day, particularly during the afternoon when the panels are no longer perpendicular to the sun. To overcome this limitation, this study proposes the design of a 50 Wp off-grid photovoltaic system equipped with a linear actuator-based solar tracking mechanism and a portable support frame. The research aims to develop an alternative renewable energy system capable of automatically adjusting the panel orientation to maximize solar energy absorption, improve electrical output, and accelerate battery charging. A quantitative experimental approach was employed by comparing the performance of the PLTS before and after the implementation of the solar tracker. System performance was evaluated using a Seaward photovoltaic tester and a clamp ammeter to measure voltage and current output. The results indicate that the solar panel absorbs radiant energy at a rate of 242.352 J/s, of which approximately 20% is converted into electrical energy (48.4704 W), while the remaining 80% is dissipated as heat. The developed system can operate independently for up to three hours without grid support and requires approximately 2.5 hours to fully charge the battery. Mechanical analysis confirms that the linear actuator safely withstands the applied load of 74 N, well below its allowable limit of 5,528 N. These findings demonstrate the feasibility of the proposed design as an efficient, reliable, and portable off-grid renewable energy solution.